Multi-syringe flow injection system for the determination of available phosphorus in soil samples - Almeida, M. Inês G. S. (2011)
Considering the importance of monitoring the levels of nutrients present in soils and their availability to plants, an automatic methodology is proposed based on multi-syringe flow injection analysis (MSFIA) for the spectrophotometric determination of available phosphorus in soil extracts. This fully computerized flow technique allowed the development of a flow network where sample and reagents were intercalated and sent further towards the detection system. The colorimetric determination was based on the molybdenum blue method with ascorbic acid as reducing reagent and the Egner–Riehm method was applied to extract phosphorus from soil samples. A linear calibration curve was obtained between 0.75 and 15.0mgL-1. A determination frequency of 15 h-1 was achieved, with good repeatability for 12 consecutive injections of soil extracts (RSD<1.7%). The results obtained from 12 soil samples were statistically comparable to those attained by the usual batch method.